Characterization and Activity of Digestive Enzymes in Different Sizes of Nile Tilapia (Oreochromis niloticus L.) - Rungkan Klahan; Nontawith Areechon; Ruangvit Yoonpundh; Arunee Engkagul (Agriculture and Natural Resources, 2009)
The activity of protease, amylase and lipase from the pseudostomach, upper intestine, lower intestine and liver of 5.7, 35.8 and 92.1 g male Nile tilapia (Oreochromis niloticus L.) was determined. Protease activity had an optimal pH of 12, 9 and 9 for the 5.7, 35.8 and 92.1 g fish respectively and the highest specific activity was found in the 35.8 g fish. Amylase activity had an optimal pH of 6, 7 and 2, respectively and the highest specific activity was found in the 92.1 g fish. Lipase activity had an optimal pH of 8, 7 and 8, respectively and the highest specific activity was found in the 35.8 g fish. In all sizes of tilapia, amylase activity was significantly higher in the liver than other organs (P<0.01). Protease and lipase activity in the lower and upper intestine respectively of the 5.7 and 35.8 g fish were significantly higher than in other organs (P<0.01). This study indicated that different sizes of fish had different levels of enzymatic activities. Middle-sized fish appeared to have the highest specific activity of protease and lipase, while the large fish had the highest specific activity of amylase. These results will be used as a basis for suitable feed formulation for different sizes of Nile tilapia so that optimum nutritional values and cost-effectiveness can be achieved.